Estoppel In The Irish Courts: The Ebb And Flow Of Unconscionability: Recent Developments - Breen, Oonagh (Journal of Malaysian and Comparative Law, 1999)
The Equity has been differently expressed from time to time. In Dillwyn v Llewelyn, it was expressed as operating through providing valuable consideration which in the circumstances established a contract. In Plimmer v Wellington Corporation, it was expressed as making a revocable licence irrevocable. It has also been expressed from time to time as operating by a form of estoppel. The foundation of it, however, in all these instances, is the recognition by the court that it would be unconscionable in the circumstances for a legal owner fully to exercise is legal rights.